Alpha‐L‐fucosidase‐1 is a diagnostic marker that distinguishes mucoepidermoid carcinoma from squamous cell carcinoma. Issue 2 (6th February 2019) - Ishida, Shoko; Kayamori, Kou; Sakamoto, Kei; Yukimori, Akane; Kugimoto, Takuma; Harada, Hiroyuki; Ikeda, Tohru
Abstract : Alpha‐L‐fucose is a component of glycans on the cell surface. Alpha‐L‐fucose is correlated with tumorigenesis and malignancy, and alpha‐L‐fucosidase‐1 (FUCA1), the enzyme that removes terminal α‐L‐fucose residues from glycoproteins, is downregulated in some high malignancy cancers. The expression profile of FUCA1 in head and neck tumors remains unknown, and we analyzed the expression profiles of FUCA1 and an upstream molecule p53 in mucoepidermoid carcinoma (MEC) and oral squamous cell carcinoma (OSCC). FUCA1 was expressed in most MECs irrespective of histopathological grading, whereas expression in OSCCs was low. High immunohistochemical intensity of p53 was detected in OSCCs at high frequency, but rarely detected in MECs. Genetic mutation analysis using next‐generation sequencing revealed no significant mutation of TP53 in MECs. We further analyzed the expression profiles of FUCA1 in normal major and minor salivary glands and found strong expression in the intercalated duct, moderate expression in mucous acinar cells and no expression in serous acinar cells. These contrasting immunohistochemical profiles and anatomical distribution in normal salivary glands suggest that FUCA1 is a useful marker to distinguish MEC from OSCC, and many MECs have similar immunohistochemical phenotypes to intercalated duct and mucous acinar cells.